PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA DALAM PEMBELAJARAN SEJARAH KONTROVERSIAL MELALUI METODE DEBAT PADA SISWA KELAS XI IPA 2 DI SMA NEGERI 1 TUNTANG TAHUN AJARAN 2009/2010 (Paramita: Historical Studies Journal, 2011)
Controversial history learning has not been implemented optimally so that critical thinking skills of students is still low. This is evidenced by the low ability of studentsâ€™ critical thinking of class XI IPA 2 SMA Negeri 1 Tuntang in controversial history learning. This type of research is the Classroom Action Research with phase of activity which consists of two cycles. Research data obtained by using interviews, questionnaires and observation with the observation sheet and through evaluation tests. Data analysis techniques is done before, during and after learning. The Point of analysis is students critical thinking ability when learning, and critical abilities of students in work on the problems of evaluation. The results showed that through the methods of teaching history in a controversial debate, there is a discernable increase of critical thinking skills of students class XI IPA 2 SMA Negeri 1 Tuntang. Observations during the learning process showed that students eager to follow learning through debate because the debate is something new for students. Keywords: Critical Thinking, Controversial History, Method debate Â